Taming Trees, Shaping Forests, and Managing Woodlands as Resources for Understanding Past Societies. Contributions and Current Limits of Dendro-Anthracology and Anthraco-Isotopy - Dufraisse, Alexa; Coubray, Sylvie; Picornell-Gelabert, Llorenç; Alcolea, Marta; Girardclos, Olivier; Delarue, Frédéric; Nguyen Tu, Thanh-Thuy (Frontiers in Ecology and Evolution, 2022)
In many societies, livelihood strategies are based on a combination of economic strategies, including natural resources such as trees for wood, leaves, and fruits. Archeological wood charcoals are residues of human activity related to fire. They provide evidence of fuelwood and, in some contexts, timber, handcraft activities, and fruit production. They represent a detailed record of the way ancient woodlands were exploited. However, charcoal analyses are often confined to the study of taxa and their relative frequency, and socio-economic interpretations are thus limited. In the last two decades, dendro-anthracological studies have been developed. Tree-ring widths, radius of curvature, and carbon isotope contents are increasingly used as indicators of wood gathering practices, woodland management and climate. Nevertheless, in the absence of standards, measurement procedures and data processing are very diverse. The challenge for archeological charcoal analyses is thus to improve analytical tools, especially on dendro-anthracological and isotopic aspects, in order to improve the interpretation of archeological assemblages and advance the discipline. As an example, we present a new approach for taxa growing in Western Europe combining (i) different dendro-anthracological parameters, (ii) an anthraco-typological approach based on modern-day wood stands, (iii) identification of anatomical signatures revealing particular forestry practices, and (iv) stable carbon isotopes. This opens the discussion on methodological perspectives and the associated scientific questions focusing on woodland exploitation and climate, and on the interest of a systemic approach for the analysis of charcoal in archeological contexts.